The Best of Both Worlds: A Proposal for Hybrid Teacher Education - Vininsky, Hayley; Saxe, Amanda (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2016)
Recent advances in technology have created a surge in online educational opportunities, increasing accessibility to education. However, online learning suffers from criticism that these courses are substandard in comparison to traditional classes, despite research that suggests otherwise. We discuss our personal experiences with traditional and online education, highlighting their advantages and disadvantages. Guided by the Universal Design for Learning (UDL) framework, we propose the development of a hybrid teacher education program that utilizes the best facets of both traditional and online education.